PENGARUH FAMILY CONTROL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA INDUSTRI DASAR DAN KIMIA - Ivana Teddy Kusumawati (Business Accounting Review, 2014)
Family firms are still dominating in Indonesia,and they have advantages and disadvantages which affecting the firm’s performance. According to many previous researches about the influence of family control, there were still a lot of unconsistent results. This study aimed to know the influence of family control on profitability and firm’s value. The measurement of the profitability was measured by using ROA and firm’s value by using Tobin’s Q. The Control variables used were size, sales growth, and leverage. The sample used in this research were firms in the sector of basic and chemical industry which fulfilled certain criteria and analysed by using multiple regression analysis.The results proved that family control had no influence on profitability and firm’s value. Sales growth and leverage variables also had no influence on profitability and firm’s value. Meanwhile, size variable had positive influence on profitability and negative influence on firm’s value.